Validation and Classification of Atypical Splicing Variants Associated With Osteogenesis Imperfecta - Li, Lulu (Front Genet, 2019)
Osteogenesis Imperfecta (OI) is a rare inherited bone dysplasia, which is mainly caused by mutations in genes encoding type I collagen including COL1A1 and COL1A2. It has been well established to identify the classical variants as well as consensus splicing-site-variants in these genes in our previous studies. However, how atypical variants affect splicing in OI patients remains unclear. From a cohort of 867 OI patients, we collected blood samples from 34 probands which contain 29 variants that are located close to splice donor/acceptor sites in either COL1A1 or COL1A2. By conducting minigene assay and sequencing analysis, we found that 17 out of 29 variants led to aberrant splicing effects, while no remarkable aberrant splicing effect was observed in the remaining 12 variants. Among the 17 variants that affect splicing, 14 variants led to single splicing influence: 9 led to exon skipping, 2 resulted in truncated exon, and 3 caused intron retention. There were three complicated cases showing more than one mutant transcript caused by recognition of several different splice sites. This functional study expands our knowledge of atypical splicing variants, and emphasizes the importance of clarifying the splicing effect for variants near exon/intron boundaries in OI.